IMPLEMENTASI METODE FORWARD CHAINING PADA SISTEM PAKAR UNTUK DIAGNOSA MASALAH GIZI PADA IBU HAMIL BERBASIS WEB - Nurunnisa, Bagus Wahyu Pandhito, Suhendra Anjar Dinata (Sekolah Tinggi Ilmu Komputer El Rahma, 2024)
The study aims to develop a system of web-based experts that diagnose the nutritional problems of expectant mothers. The system uses forward chaining methods as a mechanism of inference to reach diagnostic conclusions. By inducing the symptoms of an expectant mother, the system will automatically search out and match the symptoms to a defined basis of knowledge. The end result of this process is the diagnosis of the nutritional problems the expectant mother may experience. It is hoped to be an aid to health-care workers and expectant mothers in providing the right initial diagnosis and treatment recommendations.